New Constituent from Fruits of Lycium chinense Miller - Chung, Ill-Min; Yang, Ye-Seul; Ahmad, Ateeque (Asian Journal of Chemistry, 2014)
One new compound a-D-glucopyranosyl-(2®1')-a-L-arabinopyranosyl-(2'®1'')-a-Larabinopyranosyl-(2''®1''')-a-L-arabinopyranoside (1) was isolated and identified from the fruits of Lycium chinense. The chemical structure of new compound was elucidated by 1D and 2D NMR spectroscopic techniques (COSY, HMBC and HSQC) aided by FABMS and IR spectra and chemical reactions.